2008
DOI: 10.1590/s1516-89132008000700026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an extract of Juglans regia on the growth of Escherichia coli, on the electrophoretic profile of plasmid DNA and on the radiolabeling of blood constituents

Abstract: The aim of this work was to study the influence of a walnut (Juglans regia) extract on the growth of Escherichia coli (E. coli) AB1157

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…In recent studies, it was reported; the genotoxic and cytotoxic effects of SnCl 2 can be altered by herbal extract, chemicals and pharmaceutics on E. coli 5,8,[10][11][12][13] . One of these studies was performed by using cauliflower which is in the same family with broccoli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, it was reported; the genotoxic and cytotoxic effects of SnCl 2 can be altered by herbal extract, chemicals and pharmaceutics on E. coli 5,8,[10][11][12][13] . One of these studies was performed by using cauliflower which is in the same family with broccoli.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, some authors have also described that genotoxic and cytotoxic effects of SnCl 2 can be altered by herbal extract, chemicals and pharmaceutics on E. coli 5,6,[8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…1 Las hojas son consideradas fuente de compuestos saludables y han sido usadas ampliamente en la medicina tradicional para el tratamiento de dermatitis, insuficiencia venosa y úlceras; y posee propiedades antidiarreica, antihelmíntica, antiséptica, antibacteriana, astringente, antioxidante, antifúngico, hipoglicémica y antiproliferativa. [2][3][4][5][6] En el Perú las hojas se usan como astringente, en lavados uterinos, para lavar heridas, con leche para tratar la tos y como cataplasma para las articulaciones hinchadas. El cocimiento del fruto fresco como enjuagatorio para las llagas y úlceras en la cavidad bucal.…”
Section: Introductionunclassified